Multipliers and imperfect competition: what is the role of capital depreciation? - Costa, Luís F. (2000)
In static general equilibrium models considering imperfectly competitive goods markets, the effectiveness of fiscal policy to stir output is shown to be greater than in the walrasian case. However, labour is the only input in these models. Here, I develop a simple intertemporal model allowing us to study the steady-state role of optimal capital stock in the fiscal policy transmission mechanism. I demonstrate the results depend strongly on the set of parameter values chosen and on the output definition. Using plausible numerical values the multiplier is larger in the walrasian case for small initial government purchases, and smaller for intermediate values.